Measurement of Breast Tissue Estrogens by Liquid Chromatography-Tandem Mass Spectrometry - Olisov, D.A.; Chagovets, V.V; Starodubtseva, N.L.; Smetnik, A.A.; Rodionov, V.V.; Kometova, V.V.; Chingin, K.S.; Frankevich, V.E. (Biomedical Chemistry: Research and Methods, 2021)
Although estrogen contribution estrogen to breast cancer development is not fully understood, an effective method of their measurement, in the mammary gland might provide additional insight. In this study, we have developed a LC-MS/MS method of simultaneous quantification of estrone and estradiol in breast tissue samples. Analytes were extracted with methyl tert-butyl ether by sonication and derivatized with dansyl chloride. Estrogens were analyzed by liquid chromatography-tandem mass spectrometry with an electrospray ionization source. Accuracy and precision were better than 20% for most concentrations. Although estrone and estradiol levels in normal and malignant breast tissue samples analyzed using our method insignificantly differed. The method developed may be used in further studies aimed at evaluating a role estrogens in breast cancer risk.